Evaluation of Risk Factors and Outcome of Incarcerated Inguinal Hernia in Pediatric Age Group - Ibrahim Tariq Ameen1, Raid Hamid Abdul-Ghafoor2, Bilal Hamid Abdul-Ghafoor3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Incarcerated inguinal hernia is one of emergency conditions in children. It results from entrapment of bowel or other viscera within the hernia sac. High incidence of incarcerated inguinal hernia occurs in young age and preterm. The incidence of incarcerated hernia is variable and ranges from 12–17%. The aim is to evaluate the risk factor / or factors and outcomes for patients with incarcerated inguinal hernia.Patients and method: This prospective study directed in department of pediatric Surgery, Central Child’s Teaching Hospital, Baghdad, Iraq. Fifty-five patients with incarcerated inguinal hernia were managed for 10 months. They were evaluated for history and sent for investigations. All patients initially treated by manual reduction. Later on they treated by elective operation. Overall outcomes were evaluated in all patients.Results: The patient`s age range from 17 days to 5.5 years. There was male predominance with male: female ratio was 10:1. The frequency of right side incarcerated inguinal hernia was more than the left. Fourty (72.7%) patients were under first year. Thirty-two (58.2%) patients were preterm. Fourty-four (80%) patients have successful manual reduction and eleven (20%) patients were failed and underwent emergency surgery. Intestinal resection done to 4 patients and rate was 7.3%, and orchiectomy done to 3 patients and rate was 5.4%.Conclusion: Premature and younger age patients are risk factors for incarcerated inguinal hernia. Incarceration increases the rate of overall complications. Any patient, especially young patient and preterm, with reducible hernia should be treated as soon as possible.